2020
DOI: 10.1111/gcb.15119
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns and controlling factors of soil nitrification rate

Abstract: Soil nitrification, an important pathway of nitrogen transformation in ecosystems, produces soil nitrate that influences net primary productivity, while the by‐product of nitrification, nitrous oxide, is a significant greenhouse gas. Although there have been many studies addressing the microbiology, physiology, and impacting environment factors of soil nitrification at local scales, there are very few studies on soil nitrification rate over large scales. We conducted a global synthesis on the patterns and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(119 citation statements)
references
References 75 publications
12
104
0
3
Order By: Relevance
“…Moreover, soil organic N can increase soil microbial biomass and subsequently increase N mineralization (Liet al 2019). A recent study revealed that the content of soil total N is the main driver for soil nitrification rate at the global scale (Li et al 2020). In line with our finding, a recent study revealed that manure application also substantially increases N 2 O emission by 5.1-58.2% (Zhou et al 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, soil organic N can increase soil microbial biomass and subsequently increase N mineralization (Liet al 2019). A recent study revealed that the content of soil total N is the main driver for soil nitrification rate at the global scale (Li et al 2020). In line with our finding, a recent study revealed that manure application also substantially increases N 2 O emission by 5.1-58.2% (Zhou et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Of climatic factors, higher temperature usually motivates soil N 2 O emission in terrestrial ecosystems through denitrification (Zhang et al 2019c;. Mean annual temperature also significantly influences soil nitrification on the global scale (Li et al 2020), which may eventually impact global soil N 2 O emission. Since water condition affect both nitrification and denitrificationvia altering soil oxygen availability (Bollmann & Conrad 1998), higher soil water content significantly increases soil N 2 O emission (Wu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Soil nitrate nitrogen (NO 3 --N) and NH 4 þ -N not only provides essential nutrients for microbes but also indirectly affects soil microbes and gas emissions. The process of nitrification and denitrification was affected by the soil pH and affected the activity of soil microbes (Sauze et al 2017;Li et al, 2020). Furthermore, denitrifying intermediates can inhibit methanogenic microorganisms during nitrate reduction (Clarens et al, 1998;Bao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fewer plant litters introduce into soil because of the ingestion of livestock, which could make these soil dwellers hard to survive (Bardgett, Denton, and Cook 1999). In addition, low-temperature can restrict the decomposition rate of matter in alpine meadow ecosystems (Xu et al 2013;Li et al 2020b). Consequently, the supply of soil available nutrients would become unsustainable.…”
Section: The Beginning Of Meadow Degradationmentioning
confidence: 99%